Athenry Dominican Priory, south nave wall, niche, base - O'Donovan, Danielle (My University, 2008)
Base of eastern niche in south nave wall, from top down moulding comprises: roll, bell, roll and fillet, roll, plinth.
Niche
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Late Medieval; roll-and-fillet moldings; roll moldings; plinth